PENERAPAN TEKNIK LAY UP SHOOT DALAM PEMBELAJARAN PJOK BOLA BASKET DI SMA NEGERI 1 POLEWALI MANDAR - Irawati, Andi Febi (Journal of Sport Science And Physical Education (JOSEPHA), 2025)
This research is a type of quantitative descriptive research descriptive quantitative research that aims to analyze the application of lay up shoot in basketball PJOK learning at SMA Negeri 1 Polewali Mandar. The subjects of this study were students of SMA Negeri 1 Polewali Mandar, with a total sample of 20 people. Sample of 20 people. Data collection is done through lay up shoot. The data obtained was analyzed using statistical techniques descriptive statistical techniques based on percentage. The results showed that of the 20 students (100%) who were sampled, there were no students who were in the category (0%), 9 students (45%) are in the good category, 5 students (25%) in the moderate category, 4 students (20%) in the deficient category, 4 students (20%) in the poor category. (25%) in the moderate category, 4 students (20%) in the less category, and 2 students (10%) in the very poor category. (10%) were in the very poor category.